Targeting Impaired Nutrient Sensing via the Glycogen Synthase Kinase-3 Pathway With Therapeutic Compounds to Prevent or Treat Dementia: A Systematic Review - Matysek, Adrian; Kimmantudawage, Sumudu Perera; Feng, Lei; Maier, Andrea B. (Frontiers in Aging, 2022)
Background: Dementia is a global challenge with 10 million individuals being diagnosed every year. Currently, there are no established disease-modifying treatments for dementia. Impaired nutrient sensing has been implicated in the pathogenesis of dementia. Compounds that inhibit the glycogen synthase kinase-3 (GSK3) pathway have been investigated as a possible treatment to attenuate the progression of the disease, particularly the suppression of the hyper-phosphorylation process of the tau protein. Aims: Systematically summarizing compounds which have been tested to inhibit the GSK3 pathway to treat cognitive impairment and dementia. Methods: PubMed, Embase and Web of Science databases were searched from inception until 28th July 2021 for articles published in English. Interventional animal studies inhibiting the GSK3 pathway in Alzheimer's disease (AD), Parkinson's dementia, Lewy body dementia, vascular dementia, mild cognitive impairment (MCI) and normal cognitive ageing investigating the change in cognition as the outcome were included. The Systematic Review Centre for Laboratory animal Experimentation’s risk of bias tool for animal studies was applied. Results: Out of 4154 articles, 29 described compounds inhibiting the GSK3 pathway. All studies were based on animal models of MCI, AD or normal cognitive ageing. Thirteen out of 21 natural compounds and five out of nine synthetic compounds tested in MCI and dementia animal models showed an overall positive effect on cognition. No articles reported human studies. The risk of bias was largely unclear. Conclusion: Novel therapeutics involved in the modulation of the GSK3 nutrient sensing pathway have the potential to improve cognitive function. Overall, there is a clear lack of translation from animal models to humans.